2014
DOI: 10.1002/2014gb004846
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical control of marine productivity in the Mediterranean Sea during the last 50 years

Abstract: The temporal dynamics of biogeochemical variables derived from a coupled 3-D model of the Mediterranean Sea are evaluated for the last 50 years (1960–2010) against independent data on fisheries catch per unit effort (CPUE) for the same time period. Concordant patterns are found in the time series of all of the biological variables (from the model and from fisheries statistics), with low values at the beginning of the series, a later increase, with maximum levels reached at the end of the 1990s, and a posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 43 publications
(86 reference statements)
5
46
0
Order By: Relevance
“…In addition, our results indicated that the PP anomaly, representing the temporal variation of the primary productivity of the system, was the strongest driver upon the Mediterranean Sea ecosystem. This supports the results obtained from other studies4957 that have shown how the Mediterranean Sea is driven by bottom-up processes where nutrient availability controls the biological characteristics of the region. The use of relative PP trends from a regional biogeochemical model helped validating our predicted PP anomaly trend and improved the temporal dynamics of selected species in the ecosystem (particularly for forage fish: European pilchards and anchovies).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our results indicated that the PP anomaly, representing the temporal variation of the primary productivity of the system, was the strongest driver upon the Mediterranean Sea ecosystem. This supports the results obtained from other studies4957 that have shown how the Mediterranean Sea is driven by bottom-up processes where nutrient availability controls the biological characteristics of the region. The use of relative PP trends from a regional biogeochemical model helped validating our predicted PP anomaly trend and improved the temporal dynamics of selected species in the ecosystem (particularly for forage fish: European pilchards and anchovies).…”
Section: Discussionsupporting
confidence: 91%
“…GETM is coupled online to the MedERGOM biogeochemical model (Macias et al a,b ) by using the Framework for Aquatic Biogeochemical Models (FABM, https://sourceforge.net/projects/fabm/, Bruggeman and Bolding ). MedERGOM is a modified version of the ERGOM model (Neumann ) specifically adapted to represent the conditions of the pelagic ecosystem of the Mediterranean Sea.…”
Section: Methodsmentioning
confidence: 99%
“…MedERGOM is a modified version of the ERGOM model (Neumann ) specifically adapted to represent the conditions of the pelagic ecosystem of the Mediterranean Sea. It has proven useful to describe present (Macías et al b ), past (Macias et al a ), and future (Macias et al ) biogeochemical conditions in this semi‐enclosed basin. MedERGOM includes three phytoplankton types, three macronutrients (nitrate, ammonia, and phosphate), detritus and dissolved oxygen as main state variables.…”
Section: Methodsmentioning
confidence: 99%
“…No horizontal currents were imposed at the open boundary. It has been demonstrated that for basinwide studies the location of this western boundary is not crucial (e.g., Macías et al 2013Macías et al , 2014c, but it does affects the performance of the model in the Alboran Sea in terms of absolute values of hydrological and biogeochemical properties (e.g., Macías et al 2014b). In those previous works, the open boundary of the model was located right on the strait itself as their focus was on the basin-wide properties and not on regional scales.…”
Section: Model Descriptionmentioning
confidence: 99%